Experimental and numerical investigation on the possibility of no-vent filling of liquefied natural gas. (September 2019) - Kim, Kyoung Joong; Jin, Lingxue; Jeong, Sangkwon; Yang, Hyung Suk; Yoo, Jaeun; Choi, Yeon Suk
Highlights: The numerical model of no-vent filling is verified with ten experiment conditions. The prediction model considers thermodynamic nonequilibrium states. We have demonstrated that NVF can be applicable to actual LNG cargo tank. Operational conditions, including the transfer line chill-down effect, are presented. Abstract: To examine the applicability of no-vent filling (NVF) as an LNG charging method, we carried out numerous cryogenic experiments with tetrafluoromethane (CF4 ) and octafluoropropane (C3 F8 ). A numerical calculation was also conducted by the prediction model established in the previous research. As a result, the average bottom temperature was predicted within the error of 3.2%, and the tank pressure was simulated with the maximum error of 11%. In addition, we have found the NVF conditions that will ensure the maximum pressure during the fluid transfer process below the allowable pressure of Type A and Type B LNG tanks.